Investment in resilient food systems in the most vulnerable and fragile regions is critical - (:unkn) unknown (My University, 2021)
Reversing the alarming trend of rising food insecurity requires transformations towards just, sustainable and healthy food systems with an explicit focus on the most vulnerable and fragile regions.
Keywords: African Research